Performance measurement of Public Works Department on the basis of Key Performance Indicator regarding compliance to PPA (2006) & PPR (2008): case study on construction of Bangladesh Television Bhaban (BTV) at Rampura, Dhaka. - Mahmood, Mirza Shibli (BRAC University, 2018)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2016.